STRATEGY TO INCREASE PUBLIC CONFIDENCE IN ATTRACTING UMRAH PILGRIMAGES - Zainur Ridho; Farida dewi; Nadila vega (IZZI: Jurnal Ekonomi Islam, 2025)
As time goes by, building a service business can be said to have very bright prospects, especially in line with changing consumer patterns that are increasingly diverse and prioritize convenience. A strategy consists of several tactics. Strategies are general, fundamental, and long-term, compared to tactics, which are more specific, operational, and short-term plans. Strategy aligns with the development of the concept of strategic management, which is not simply defined as a means to achieve a goal.Trust is closely related to religion, but its scope is broader.Increasing public trust in attracting pilgrims to register with PT Qiblatain travel is a crucial step to expand reach and increase customer numbers. This includes providing clear information, such as package prices, facilities, and registration requirements, clearly and transparently. Good and friendly service is also essential for providing services to PT Qiblatain pilgrims. By implementing a strategy that focuses on information transparency, service quality, legality, education, digital marketing, attractive promotions, and community development, PT Qiblatain can build a strong reputation in the eyes of the public.